Biochemical and pharmacological effects of mitoxantrone and acetyl-L-carnitine in mice with a solid form of Ehrlich tumour - Niang, M; Soukup, T; Zivný, P; Tomšík, P; Bukač, J; Rezáčová, M; Stoklasová, A; Cerman, J; Sišpera, L (Chemotherapy, 2011)
BACKGROUND: Dysfunction of the carnitine system in non-tumour tissue following anticancer therapy has been reported. In this setting, supplementation with carnitine derivatives might increase the general metabolic activity of normal cells so that they might better withstand the adverse effects of chemotherapy aimed at tumour cells. Here we investigated the effect of acetyl-L-carnitine (ALC) alone and in combination with the antineoplastic agent mitoxantrone (MX) in an animal cancer model. METHODS: The effects of MX and MX-ALC were assessed based on gain or loss of body weight and on local growth of a solid form of Ehrlich tumour inoculated into mice. We also performed biochemical analyses like serum activities of some enzymes signalling the functioning of the liver, aspartate aminotransferase (AST), and alanine aminotransferase (ALT). Total protein, albumin and bilirubin were also determined in serum. Under favourable conditions, the Ehrlich tumour readily forms metastases, and this is the reason why we performed histological studies of samples of both the liver and heart in order to identify changes that may have mediated the observed effect of the treatment. In addition to those studies, the survival time of treated animals against controls was also noted. RESULTS: MX monotherapy was associated with lower body weight gain, fewer metastases, smaller tumour size, and lower dissemination. ALC alone promoted survival, but had no potentiating effect on MX therapy in terms of survival. Serum biochemistry changes associated with MX-ALC treatment consisted of a significant (p < 0.05) increase in AST with MX at 6 or 9 mg·kg(-1) plus ALC 200 mg·kg(-1) and a significant (p < 0.05) reduction in total protein compared to the corresponding MX group; serum albumin and bilirubin remained unchanged. CONCLUSION: ALC in combination with MX, regardless of the dose of MX, led to higher occurrences of metastases with dissemination to the kidneys, lungs, heart, and mediastinum compared to MX treatment alone. These histological findings indicate that ALC is inappropriate to combine with MX in the treatment of a solid cancer. The protective effect of ALC in combination therapy with the cytostatic drug MX was not supported in this study by our findings that the agent did not improve the therapeutic outcomes of MX therapy.
Keywords: mitoxantron; Ehrlichův tumor; Carcinoma, Ehrlich Tumor; Acetylcarnitine; sérový albumin; Mice; Antineoplastic Agents; Body Weight; Serum Albumin; ženské pohlaví; protinádorové látky; zvířata; Bilirubin; tělesná hmotnost; myši; bilirubin; Female; Mitoxantrone; acylkarnitin; Liver Neoplasms, Experimental; experimentální nádory jater; Animals